Reproductive health literacy scale: a tool to measure the effectiveness of health literacy training - Maha Rauf; Zahra Goliaei; Lana Machta; Jenny Chang; Heike Thiel de Bocanegra (Reproductive Health)
Abstract Background Refugee women’s reproductive health (RH) outcomes have been impacted by several factors, including experiencing war, lack of access to healthcare, and possible gender-based violence. After resettlement, low health literacy, financial difficulties, cultural and linguistic barriers, and unfamiliarity with the healthcare system also add to the preexisting barriers. Although several efforts have focused on health education and improving health literacy among refugee women, there has not been a validated tool to measure the effectiveness of these trainings and their possible impact. This study aims to adapt a culturally and linguistically appropriate survey that helps address this gap. Methods We conducted a literature review to identify the existing tools and identified possible domains and items supporting RH literacy measures. The identified items were collected and adapted as a single scale with three domains: (a) general health literacy, measured with HLS-EU-Q6, (b) digital health literacy, measured with eHEALS, and (c) reproductive health literacy, measured through a composite of the Cervical Cancer Literacy Assessment Tool (C-CLAT) and the Refugee Reproductive Health Network (ReproNet) postpartum literacy scale. After content validity and face validity of the adapted scale, it was translated into Dari, Arabic, and Pashto and was administered to participants of RH literacy training sessions. Results A total of 67 Dari, 53 Arabic, and 64 Pashto-speaking refugee women completed the survey. The mean scores obtained between the three language groups were similar in the domains of digital health literacy and reproductive health literacy (p > 0.05), whereas the scores for general health literacy were not (p > 0.05). The inter-item reliability score for the domains of general health literacy, digital health literacy and RH literacy across all three language groups was above α = 0.7. Conclusion This scale addresses the need for validated tools to measure reproductive health literacy. It has the promise to provide a tool for assessing the effectiveness of health interventions on health literacy. Future applications can utilize this scale to investigate the differences in health literacy in refugee populations speaking Dari, Pashto, and Arabic.